INTERNAL COMMUNICATION AND EMPLOYEE ENGAGEMENT IN FEDERAL TERTIARY INSTITUTIONS IN RIVERS AND BAYELSA STATES - Eke, Chigozi; Adeyemi, Opeyemi Muideen (African Journal of Social and Behavioural Sciences, 2024)
This study examined the internal communication and employee engagement in Federal tertiary institutions in Rivers and Bayelsa States. The objectives of the study were among others to investigate the kind of internal communication that exists between employees and management of Federal tertiary institutions in Rivers and Bayelsa States. The study aimed to explore internal communication in four Federal tertiary institutions in Rivers and Bayelsa states, anchored on stakeholders, system and relational dialectics theories, using descriptive survey method. The population included staff and management from the four institutions, totalling 9,095 participants, with a sample size of 387 determined by the Keyton determinant table. The study adopted the multi-stage sampling technique, data were obtained using questionnaire and analysed using the weighted mean score based on a four-point Likert scale. The findings revealed that, the kind of internal communication that existed between employees and management of federal institutions in Rivers and Bayelsa States were mainly memos, emails, newsletters, meetings, suggestion boxes and employee forums. The study concluded that the predominant internal communication methods in federal tertiary institutions include memos, emails, newsletters, meetings, suggestion boxes and employee forums. The study recommended that tertiary institutions should explore integrating digital platforms and fostering more interactive communication channels.